Chemical composition, bioactive compounds, antioxidant activity, and inhibitor alpha-glucosidase enzyme of Sargassum sp. - DIHARMI, Andarini; EDISON, EDISON; PRIDA, Elsa A; SUBARYONO, SUBARYONO; HIDAYAT, Taufik (Food Science and Technology, 2023)
Sargassum sp. has the potential to be a source of bioactive components. The purpose of this study was to determine the chemical composition, bioactive compounds, antioxidant activity, and α-glucosidase enzyme inhibitory activity of Sargassum sp. extract. The exploratory research method involved extracting Sargassum sp. for 72 h using solvents of different polarities. The chemical composition of Sargassum sp. was analyzed using parameter analysis as well as the identification of phytochemicals and total phenolics. Antioxidant activity was measured using the DPPH method as well as inhibition of α-glucosidase enzyme activity. The chemical composition of Sargassum sp. was found to be 15.67, 17.56, 13.46, 0.6, 57.82, and 13.62% moisture content, ash, protein, fat, carbohydrates (by difference), and total crude fiber, respectively. The bioactive compounds of Sargassum sp. include saponins and phenolic compounds that were extracted with methanol (617.778 GAE/100 g) and ethyl acetate (309.55 GAE/100 g). The antioxidant activity with IC50 value of Sargassum sp. extract successively extracted 648.33 mg/mL of methanol, 864.22 mg/mL of ethyl acetate, and 884 mg/mL of n-hexane. Sargassum sp. extract inhibited the activity of α-glucosidase enzyme methanol extract (9.44–0.35%), n-hexane extract (11.72–0.46%), and ethyl acetate did not. Except for the ethyl-acetate extract, Sargassum sp. extract has antioxidant and enzyme α-glucosidase inhibitor properties.